Effect of Graded Levels of Baobab (Adansonia digitata) Seed Meal on the Growth Performance and Production Economic Analysis of Broiler Chickens - Bale , Jerry Sarven; Mancha, Yusuf Pam; Sanusi, Mohammed; Doma, Umar Dass (International Journal of Poultry Science, 2013)
A feeding trial was conducted to determine the effect of graded levels of baobab seed meal on growth performance and cost benefit in broiler chicken production. A total of two hundred one-week old broiler chicks of the Anak breed were randomly distributed to five dietary treatments and replicated four times with 10 birds each for a period of 8 weeks. Baobab seed meal was included in the broiler chicken diets at 0, 10, 20, 30 and 40% levels designated as diets 1, 2, 3, 4 and 5, respectively for both the starter and finisher phases. At the starter phase, feed intake (65.18-71.73 g), daily weight gain (30.36-36.16 g) and feed conversion ratio (1.96-2.39) were not significantly (p>0.05) affected by the dietary treatments. However, at finisher phase, the daily feed intake (133.40-148.40 g) and weight gain (37.23-55.00 g) were significantly affected at (p<0.001) and (p<0.05) respectively. Feed conversion ratio was not significantly (p>0.05) different among all the treatments means. The overall performance showed significant difference at (p<0.001 and p<0.01) for daily feed intake and daily weight gain, respectively. The birds fed 20% diet had the highest daily weight gain (44.55 g) and lowest (33.80 g) was recorded for diet 5. The feed cost per gain (N/kg gain) was cheaper (N142.44) on diet 4 and most expensive (N163.69) on diet 1 during the starter phase, while at the finisher phase diet 5 was cheaper (N176.36) and diet 1 being the most expensive (N193.91). Similar trends were obtained at the overall phase. It was therefore concluded that baobab seed meal can be incorporated into broiler chicken diets up to 30% without any deleterious effect on performance with concomitant reduction in feed cost.